2018
DOI: 10.3389/fneur.2018.00779
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Protection of Hydrogen Sulfide on Cerebral Ischemia/Reperfusion Injury in Rats

Abstract: This study was undertaken to demonstrate the vascular protection of exogenous and endogenous hydrogen sulfide (H2S) on cerebral ischemia/reperfusion (I/R) injury. The effect of H2S on cerebrovascular dysfunction in middle cerebral artery (MCA) and neuronal damage were measured after cerebral I/R induced by transient middle cerebral artery occlusion (MCAO) in cystathionine c-lyase (CSE) knockdown and wild-type rats. The effect of sodium hydrosulfide (NaHS, donor of exogenous H2S), L-cysteine (L-Cys, substrate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…For OGD/R (Chen et al, 2013), hippocampal neurons were subjected to 4 h of hypoxia induced by replacing culture medium with glucose‐free D‐Hank's solution (in mg·L −1 : 8000 NaCl, 400 KCl, 510 Na 2 HPO 4 ·12H 2 O, 60 KH 2 PO 4 and 350 NaHCO 3 , pH 7.2–7.4) under the condition of 94% N 2 , 5% CO 2 and 1% O 2 and 24 h of reoxygenation induced by replacing the glucose‐free D‐Hank's solution with normal culture medium and being incubated under normal condition. In NaHS or the other drug treatment groups, cells were respectively treated with NaHS (1 × 10 −6 M) (Wen et al, 2018), iberiotoxin (100 nM) (Guo et al, 2020), BMS‐191011 (10 ÎŒM) (Levin et al, 2016), NNC 55‐0396 (100 ÎŒM) (Angstadt et al, 2017) or verapamil (100 ÎŒM) (Tang et al, 2016) before and during OGD/R.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For OGD/R (Chen et al, 2013), hippocampal neurons were subjected to 4 h of hypoxia induced by replacing culture medium with glucose‐free D‐Hank's solution (in mg·L −1 : 8000 NaCl, 400 KCl, 510 Na 2 HPO 4 ·12H 2 O, 60 KH 2 PO 4 and 350 NaHCO 3 , pH 7.2–7.4) under the condition of 94% N 2 , 5% CO 2 and 1% O 2 and 24 h of reoxygenation induced by replacing the glucose‐free D‐Hank's solution with normal culture medium and being incubated under normal condition. In NaHS or the other drug treatment groups, cells were respectively treated with NaHS (1 × 10 −6 M) (Wen et al, 2018), iberiotoxin (100 nM) (Guo et al, 2020), BMS‐191011 (10 ÎŒM) (Levin et al, 2016), NNC 55‐0396 (100 ÎŒM) (Angstadt et al, 2017) or verapamil (100 ÎŒM) (Tang et al, 2016) before and during OGD/R.…”
Section: Methodsmentioning
confidence: 99%
“…As all we know, the effective therapy of ischaemic stroke depends on a functional vasculature (Palomares & Cipolla, 2011) and especially relies on endothelial vasodilator function (Wen et al, 2019). Hence, vascular protection is regarded as an important therapeutic approach to reduce damage caused by stroke (Wen et al, 2018). Endothelium‐derived hyperpolarizing factor (EDHF), one of the naturally occurring endothelium‐derived relaxing factors (EDRFs), has been found to play a crucial role in mediating blood vessel dilation (Wang, Hu, et al, 2016) and has been suggested as a therapeutic target for ischaemic brain injury (Han et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, H 2 S has been reported to improve the integrity of the barrier and attenuate cerebral edema, and the reduction of CSE expression close to injury sites coincided with increased Alb extravasation and barrier dysfunction [ 29 , 30 , 31 ]. Denoix et al reported that OTR and CSE were also expressed in the arteries and microvasculature, suggesting that they might play a role in blood–brain barrier integrity [ 25 ].…”
Section: The Neuroendocrine Control Of Fluid Hemostasismentioning
confidence: 99%
“…As substrate of H 2 S synthase, l -cysteine, could protect neonatal mice against hypoxia-ischemia injury by inhibiting glial activation . Our previous study revealed that endogenous H 2 S produced by CSE could suppress the RhoA/ROCK signaling pathway and then exert vasoprotective role against acute cerebral I/R damage of mice. , But the long-term effect of CSE-derived H 2 S on the reactive astrocytes proliferation and neural functional recovery following acute cerebral I/R injury is unclear.…”
Section: Introductionmentioning
confidence: 99%